The diminishing of indigenous artistic tradition in the decorative arts of the mosques in the Malay World - Md. Sharif, Harlina (Abdullatif Al Fozan Award for Mosque Architecture and Institut Terjemahan & Buku Malaysia Berhad, 2019)
Unlike their counterparts in the Islamic mainland, the vernacular mosques of the Malay World seem to lack the ‘grandeur’ in architecture as well as in ornamentation. During the time that the Muslim world in the western part of the Malay World were achieving artistic and technological breakthrough in mosque architecture, the 17th and 18th century witnessed a period of architectural vacuum whereby no architectural development was recorded. The aim of this study is to analyse the changes taking place in the decorative arts of the mosques built between 15th to 20th century in order to understand how the decorative arts of mosques in the Malay World evolved. By following the routes of Islamisation, the study charted the development in mosque architecture and documents the changes in mosque building elements, design and decorative arts. The study highlights the period in history when the artistic creations were most prominent and the declination of local arts only to be replaced by decorative schemes introduced by Colonial administrations in the 19th and 20th century buildings.